2005
DOI: 10.1007/s00213-005-0082-8
|View full text |Cite
|
Sign up to set email alerts
|

Next-day residual effects of hypnotics in DSM-IV primary insomnia: a driving simulator study with simultaneous electroencephalogram monitoring

Abstract: The present results corroborate studies on healthy volunteers showing that residual effects of hypnotics increase with their half-lives. The results further suggest that drugs preserving physiological EEG rhythms before and during the driving simulation test 9-11 h post-dose, such as zolpidem, do not influence next-day driving abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 43 publications
4
67
2
3
Order By: Relevance
“…[24][25][26][27] However, most studies of the effect of zolpidem on driving have examined the next day residual effect and have shown no impairment when conducted eight or nine hours after ingestion. 28,29 The reason that zolpidem is often implicated in sleep-related complex behaviors is not clear, but it is the most often prescribed sleeping pill in the United States. For example, the VONA database, which captures over one-half of the US prescriptions, found that 63% of the hypnotic sedatives prescribed by primary care providers in 2007 were zolpidem or zolpidem extended release, compared to only 29% for eszopiclone and temazepam combined.…”
Section: Legal Case 4 April 2009mentioning
confidence: 99%
“…[24][25][26][27] However, most studies of the effect of zolpidem on driving have examined the next day residual effect and have shown no impairment when conducted eight or nine hours after ingestion. 28,29 The reason that zolpidem is often implicated in sleep-related complex behaviors is not clear, but it is the most often prescribed sleeping pill in the United States. For example, the VONA database, which captures over one-half of the US prescriptions, found that 63% of the hypnotic sedatives prescribed by primary care providers in 2007 were zolpidem or zolpidem extended release, compared to only 29% for eszopiclone and temazepam combined.…”
Section: Legal Case 4 April 2009mentioning
confidence: 99%
“…Six studies evaluating sleep quality reported moderately large improvement in this parameter based on SMD. 57,60,76,78,79,82 Improvement in PSG SE in the four studies included also exceeded the clinical significance threshold. 73,76,77,82 Number of awakenings (objective) fell below the clinical significance threshold.…”
Section: Discussionmentioning
confidence: 89%
“…57,59,60,70,[72][73][74][75][76][77][78][79] The overall quality of evidence was downgraded to very low due to significant heterogeneity, imprecision, and risk of publication bias. The evidence for zolpidem 10 mg was weakly in favor of its effectiveness for improving sleep onset, sleep maintenance, sleep quality, SE and TST.…”
Section: Discussionmentioning
confidence: 99%
“…It has great potential for residual sleepiness in the morning. 10 Zaleplon is a pyrazolopyrimidine, has the ultrashort half-life (1 hr), and binding similar to zolpidem (GABA A receptors) and its main indication is for rapid induction of sleep, with little effect on its maintenance and can be used in the middle of the night, in cases of early awakening. 9 Zolpidem and zaleplon slightly alter the structure of sleep, are well-tolerated and are associated with little occurrence of tolerance and dependence with prolonged use.…”
Section: Second Generation Hypnotics (Z-drug Hypnotics)mentioning
confidence: 99%